Configuring Identities Through Industrial Architecture and Urban Planning - Rentetzi, Maria (Science Studies, 2008)
In the late nineteenth century the city of Kavala, a town by the sea in northern Greece, was developed to one of the most important tobacco processing centers in the Balkan area. Powerful tobacco merchants mainly from the Hapsburg and Ottoman empires built a considerable number of tobacco warehouses thus redefining the center of the city, its character, as well as its borders. I argue that the architecture of those warehouses deeply configured the identities of tobacco workers and provided the means to tobacco merchants to publicly present themselves and their achievements. At the same time those early industrial buildings subverted the boundaries between the city and the factory, shedding light on the work culture and every day lives of Greece’s tobacco workers.<br
Keywords: tobacco warehouses; architecture and technology; technology studies; industrial design; gender